Adverse Reactions to Facemasks in Health-Care Workers: A Cross-Sectional Survey - Liu N; Ye M; Zhu Q; Chen D; Xu M; He J; Li Q; Li J (Dove Medical Press, 2022)
Ning Liu,1 Min Ye,2 Qinya Zhu,2 Dingchao Chen,3 Mingmin Xu,4 Jia He,5 Qian Li,4 Jie Li6 1Outpatient Department, Zhejiang Rongjun Hospital, Jiaxing, Zhejiang Province, 314000, People's Republic of China; 2Nursing Department, Zhejiang Rongjun Hospital, Jiaxing, Zhejiang Province, 314000, People's Republic of China; 3Medical Department, Zhejiang Rongjun Hospital, Jiaxing, Zhejiang Province, 314000, People's Republic of China; 4Ultrasonic Department, Zhejiang Rongjun Hospital, Jiaxing, Zhejiang Province, 314000, People's Republic of China; 5Department of Urology, Zhejiang Rongjun Hospital, Jiaxing, Zhejiang Province, 314000, People's Republic of China; 6The Health Administration Center, Zhejiang Rongjun Hospital, Jiaxing, Zhejiang Province, 314000, People's Republic of ChinaCorrespondence: Jie Li, The Health Administration Center, Zhejiang Rongjun Hospital, Jiaxing, Zhejiang Province, 314000, People's Republic of China, Email 65017341@qq.comBackground: Coronavirus disease 2019 (COVID-19) has developed into a worldwide pandemic, which presents several challenges for frontline health-care workers (HCWs). HCWs are highly prone to various skin diseases due to prolonged use of personal protective equipment (PPE). The most frequently used type of PPE is facemasks. To effectively control adverse skin reactions, there is an urgent need for a range of preventive practices.Methods: This cross-sectional study was conducted at 12 hospitals in Zhejiang province, China. HCWs were invited to participate in the web survey. Data were extracted by two independent reviewers using a predesigned data collection form and analyzed with SPSS 20.0.Results: A total of 1147 questionnaires were collected, and of these, 1090 (95.03%) were valid and returned. The incidence of chest tightness and shortness of breath and face eczema was significantly higher in HCWs wearing N95 facemasks (41.91%; 31.62%) than in the HCWs wearing medical facemasks (38.05%, P = 0.010; 21.91%, P = 0.012). The incidence of ear pain and indentation was significantly higher in HCWs wearing hang-facemasks (83.81%) than in HCWs wearing strains-facemasks (61.19%, P < 0.001). The incidence of ear pain and indentation was significantly higher in HCWs wearing undiscriminating size code facemasks (79.88%) than in the HCWs wearing discriminating size code facemasks (67.86%, P = 0.031). There was a significant reduction (P  <   0.001) in the incidence of HCWs without adverse reactions (ADRs) with increasing time wearing facemasks.Conclusion: Incidence of ADRs does not significantly increase with the durations of mask wear where wearing mask time exceeded 4 hours per day. The medical staff generally wore masks for more than 4 hours per day; therefore, we recommend taking 15 min of rest after 2 hours of mask-wearing. Results in this study support the conclusion that the type of strain-facemasks and discriminating size code facemasks has a lower incidence of ADRs than other type of medical facemasks.Keywords: facemask, health care, COVID-19, coronavirus, dermatitis, skin care, protective equipment